Introduction to radar target recognition - Tait, Peter (London, United Kingdom Institution of Engineering and Technology, 2005)
This new text provides an overview of the radar target recognition process and covers the key techniques being developed for operational systems. It is based on the fundamental scientific principles of high resolution radar, and explains how the underlying techniques can be used in real systems, taking into account the characteristics of practical radar system designs and component limitations. It also addresses operational aspects, such as how high resolution modes would fit in with other functions such as detection and tracking.
Electronic reproduction.
Keywords: Radar; Radar targets; Target acquisition; Image processing; Imaging systems; Electronic books